Carfilzomib induction, consolidation, and maintenance with or without autologous stem-cell transplantation in patients with newly diagnosed multiple myeloma: pre-planned cytogenetic subgroup analysis of the randomised, phase 2 FORTE trial. Issue 1 (January 2023) - Mina, Roberto; Musto, Pellegrino; Rota-Scalabrini, Delia; Paris, Laura; Gamberi, Barbara; Palmas, Angelo; Aquino, Sara; de Fabritiis, Paolo; Giuliani, Nicola; De Rosa, Luca; Gozzetti, Alessandro; Cellini, Claudia; et al.
Summary: Background: Patients with newly diagnosed multiple myeloma and high-risk cytogenetic abnormalities (HRCA) represent an unmet medical need. In the FORTE trial, lenalidomide and dexamethasone plus carfilzomib (KRd) induction resulted in a higher proportion of patients with at least a very good partial response as compared with carfilzomib, cyclophosphamide, and dexamethasone (KCd), and carfilzomib plus lenalidomide maintenance prolonged progression-free survival compared with lenalidomide maintenance. In this prespecified analysis of the FORTE trial, we described the outcomes of enrolled patients according to their cytogenetic risk. Methods: The UNITO-MM-01/FORTE was a randomised, open-label, phase 2 trial done at 42 Italian academic and community practice centres, which enrolled transplant-eligible patients with newly diagnosed multiple myeloma aged 18–65 years. Eligible patients had newly diagnosed multiple myeloma based on standard International Myeloma Working Group criteria, a Karnofsky performance status of at least 60%, and had not received any previous treatment with anti-myeloma therapy. At enrolment, patients were stratified according to International Staging System stage (I vs II/III) and age (<60 years vs 60–65 years) and randomly assigned (1:1:1) to KRd plus autologous stem-cell transplantation (ASCT; four 28-day induction cycles with KRd, melphalan at 200 mg/m 2 and ASCT [MEL200-ASCT], followed by four 28-day KRd consolidation cycles), 12 28-day KRd cycles, or KCd plus ASCT (four 28-day induction cycles with KCd, MEL200-ASCT, and four 28-day KCd consolidation cycles), using a web-based system (block randomisation, block size of 12). Carfilzomib was administered at 20 mg/m 2 on days 1 and 2 of cycle 1, followed by 36 mg/m 2 intravenously administered on days 8, 9, 15, and 16 of cycle 1, and then 36 mg/m 2 intravenously administered for all subsequent doses on days 1, 2, 8, 9, 15, 16; lenalidomide 25 mg was administered orally on days 1–21; cyclophosphamide 300 mg/m 2 was administered orally on days 1, 8, and 15; and dexamethasone 20 mg was administered orally or intravenously on days 1, 2, 8, 9, 15, 16, 22, and 23. After the consolidation phase, patients were stratified according to induction–consolidation treatment and randomly assigned (1:1; block size of 8) to maintenance treatment with carfilzomib plus lenalidomide or lenalidomide alone. Carfilzomib 36 mg/m 2 was administered intravenously on days 1–2 and days 15–16, every 28 days for up to 2 years, and lenalidomide 10 mg was administered orally on days 1–21 every 28 days until progression or intolerance in both groups. The primary endpoints were the proportion of patients with at least a very good partial response after induction with KRd versus KCd and progression-free survival with carfilzomib plus lenalidomide versus lenalidomide alone as maintenance treatment. In this preplanned analysis, we included patients enrolled in the FORTE trial with complete cytogenetic data on del(17p), t(4;14), t(14;16), del(1p), gain(1q) (3 copies), and amp(1q) (≥4 copies) assessed by fluorescence in-situ hybridisation analysis on CD138-positive sorted cells. We assessed progression-free survival, overall survival, minimal residual disease negativity, and 1-year sustained minimal residual disease negativity according to the presence of zero, one, and two or more HRCA across treatment groups. The FORTE trial is ongoing, and registered with ClinicalTrials.gov, NCT02203643 . Findings: Between Feb 23, 2015, and April 5, 2017, 477 patients were enrolled, of whom 396 (83%) had complete cytogenetic data and were analysed (176 [44%] of whom were women and 220 [56%] were men). The median follow-up from first randomisation was 51 months (IQR 46–56). 4-year progression-free survival was 71% (95% CI 64–78) in patients with zero HRCA, 60% (95% CI 52–69) in patients with one HRCA, and 39% (95% CI 30–50) in patients with two or more HRCA. Compared with patients with zero HRCA, the risk of progression or death was similar in patients with one HRCA (hazard ratio [HR] 1·33 [95% CI 0·90–1·97]; p=0·15) and higher in patients with two or more HRCA (HR 2·56 [95% CI 1·74–3·75]); p<0·0001) across the induction–intensification–consolidation groups. Moreover, the risk of progression or death was also higher in patients with two or more HRCA versus those with one HRCA (HR 1·92 [95% CI 1·34–2·76]; p=0·0004). 4-year overall survival from the first randomisation was 94% (95% CI 91–98) in patients with zero HRCA, 83% (95% CI 76–90) in patients with one HRCA, and 63% (95% CI 54–74) in patients with two or more HRCA. Compared with patients with zero HRCA, the risk of death was significantly higher in patients with one HRCA (HR 2·55 [95% CI 1·22–5·36]; p=0·013) and two or more HRCA (HR 6·53 [95% CI 3·24–13·18]; p<0·0001). Patients with two or more HRCA also had a significantly higher risk of death than those with one HRCA (HR 2·56 [95% CI 1·53–4·28]; p=0·0004). The rates of 1-year sustained minimal residual disease negativity were similar in patients with zero HRCA (53 [35%] of 153] and with one HRCA (57 [41%] of 138) and were lower in patients with two or more HRCA (25 [24%] of 105). The median duration of follow-up from second randomisation was 37 months (IQR 33–42). 3-year progression-free survival from the second randomisation was 80% (95% CI 74–88) in patients with zero HRCA, 68% (95% CI 59–78) in patients with one HRCA, and 53% (95% CI 42–67) in patients with two or more HRCA. The risk of progression or death was higher in patients with one HRCA (HR 1·68 [95% CI 1·01–2·80]; p=0·048) and two or more HRCA (2·74 [95% CI 1·60–4·69], p=0·0003) than in patients with zero HRCA. Interpretation: This preplanned analysis of the FORTE trial showed that carfilzomib-based induction–intensification–consolidation regimens are effective strategies in patients with standard risk (zero HRCA) and high-risk (one HRCA) myeloma, resulting in similar rates of progression-free survival and 1-year sustained minimal residual disease negativity. Despite promising progression-free survival, patients with ultra-high-risk disease (those with 2 or more HRCA) still have an increased risk of progression and death and therefore represent an unmet medical need. Funding: Amgen and Celgene/Bristol Myers Squibb.